215k views
13 votes
Solve.
5(a – 1) – 15 = 3(a + 2) + 4
Enter your answer in the box.
X
a = 15

User MKiss
by
6.0k points

1 Answer

8 votes

Solve :

5 (a - 1) - 15 = 3 (a + 2) + 4

Solution :


\sf \dashrightarrow \: 5 (a - 1) - 15 = 3 (a + 2) + 4


\sf \dashrightarrow \: 5 * a - 5 * 1 - 15 = 3 * a + 3 * 2 + 4


\sf \dashrightarrow \: 5 a - 5 - 15 = 3 a + 6 + 4


\sf\dashrightarrow \: 5 a - 20 = 3 a + 10


\sf\dashrightarrow \: 5 a - 20 - 3a - 10 = 0


\sf\dashrightarrow \: 2 a - 30 = 0


\sf\dashrightarrow \: 2 a = 30


\sf\dashrightarrow \: a = \cancel(30)/(2)


\sf\dashrightarrow \: a = 15


\Large \underline{\boxed{\tt{a = 15 }}}

Hence, value of a = 15.

User Rudra
by
4.8k points